Development of Student Mathematics Teaching Based on Contextual Education to Improve Mathematical Literacy Ability (APPLICATION: Applied science in Learning Research, 2023)
This research aims to develop contextual-based teaching materials based on Bakmi's E-Book (Learning Algebra by Al-Khawarizmi) by going through 5 stages of ADDIE. The results showed that Bakmi's E-Book met the validity index of 81%. The percentage of material validation results is 88.1% in the Very Eligible category and media validation is 89.6% in the Very Eligible category. The test results of Bakmi's E-Book products have met the practicality index of teaching materials to be used of 96.7% in the Very Interesting category to use. In addition, Bakmi's E-Book teaching materials can also improve student learning outcomes on Algebra material. It is shown from the results of the effectiveness test through the pretest and posttest that there is an increase of 0.8% in the category of High improvement. Taking into account the results of existing research, the development of teaching materials should be carried out in a sustainable manner by holding the principle, in order to achieve the learning objectives to the maximum.